Confirmation of B-Cell Epitope of Nucleoprotein of Newcastle Disease Viruses by Dot-ELISA and Peptide ELISA - Pushpa , R.N. Ramani; Kirubaharan, J. John; Koteeswaran, A. (International Journal of Poultry Science, 2012)
A conserved B-cell epitope of nucleoprotein with the amino acid sequence “FLDLMRA” was found to be located in the conserved region between 443GETQFLDLMRAVANS457 of nucleoprotein of all four vaccine viruses used in South India. The conserved region incorporating the epitope 443GETQFLDLMRAVANS457 has been synthesized as a custom peptide. The immunodominance of the epitope was confirmed by dot-ELISA and peptide ELISA. Peptide ELISA developed using the entire conserved region was found to produce a consistent result with HI and Whole Virus Protein (WVP) ELISA. The immunodominance and immunogenicity was identified and confirmed by significant positive correlation (p<0.01) between peptide ELISA with HI and with WVP ELISA and also by Probability Plot (PP). Based on PP it could be appreciated that all points cluttered towards the expected line confirming the closeness of the results which is further strengthened by observation from ROC curves. The empirical ROC values for HI Vs Peptide ELISA and WVP ELISA VS Peptide ELISA were 0.97 and 1.00 respectively which are more than the standard value 0.8 confirming the closeness of the results proving immunodominance of the epitope and utility of the epitope to serve as a marker in DIVA vaccine.